2013
DOI: 10.1016/j.ijid.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset and late-onset group B streptococcal disease in Japan: a nationwide surveillance study, 2004–2010

Abstract: The incidence of EOD and LOD is apparently low in Japan, but the mortality and morbidity rates remain substantial. The issue of national guidelines did not affect the incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 20 publications
(39 reference statements)
2
43
2
7
Order By: Relevance
“…In accordance with a previous study (Matsubara et al, 2013), our results show that genotype distribution differs by country and region. For example, Ia, II, III, and V are the main serotypes in Europe and the United States (Skoff et al, 2009;Tazi et al, 2011), while Ia and IV are dominant in Malaysia (Karunakaran et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with a previous study (Matsubara et al, 2013), our results show that genotype distribution differs by country and region. For example, Ia, II, III, and V are the main serotypes in Europe and the United States (Skoff et al, 2009;Tazi et al, 2011), while Ia and IV are dominant in Malaysia (Karunakaran et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Patients with GBS-derived pneumonia were included, since GBS pneumonia was previously reported to be higher in developing countries (Matsubara et al, 2013). Considering the small sample size, further investigation is required to confirm our results.…”
Section: Discussionmentioning
confidence: 76%
“…6 The rate of late-onset GBS diseases in Japan remained at 0.10 per 1,000 live births through 2004-2010, which was comparable to early-onset GBS diseases. 13 Our study found more lateonset GBS diseases (46.3%) than early-onset GBS diseases (21.9%). This may be explained by sampling bias as the study was conducted at only tertiary children's hospitals, which tend to admit neonates who need surgery rather than preterm or infants with severe illness who were discharged home after birth.…”
supporting
confidence: 42%
“…12 In Japan, the rates of early-onset GBS infections did not change before and after implementation of prevention guidelines at delivery in 2008, which were 0.08 per 1,000 live births in 2004-2008 and 0.10 per 1,000 live births in 2009-2010, respectively. 13,14 The Netherlands and Japan had much lower incidence of GBS diseases than the US, so those countries with low incidence of early-onset GBS diseases might not have benefited from prevention strategy.…”
mentioning
confidence: 99%
“…20,21 A recent nationwide surveillance study in Japan has also shown that the estimated incidence of early-onset GBS disease was 0.08/1,000 live births. 22 The incidence of earlyonset GBS disease is apparently low in Japan, because the management of pregnant women with GBS based on the recommendations from the US Centers for Disease Control and Prevention (CDC) may have become standard and mostly followed in Japan. 23 Furthermore, no difference between each NICU was observed for the incidence of EOS in a study of Japanese NICUs.…”
Section: Recent Epidemiology Incidencementioning
confidence: 99%